2020
DOI: 10.1002/jhbp.823
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound guided–antegrade biliary stenting vs percutaneous transhepatic biliary stenting for unresectable distal malignant biliary obstruction in patients with surgically altered anatomy

Abstract: Background/Purpose: Unresectable distal malignant biliary obstruction (DMBO) in patients with surgically altered anatomy is traditionally managed with percutaneous transhepatic biliary drainage (PTBD) and stenting because the anatomical features complicate the endoscopic approach to the biliary orifice. EUS-guided approaches recently emerged as alternative treatments; however, limited data comparing the procedures are available. The aim of this study was to compare EUS-antegrade biliary stenting (ABS) with PTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…A 66‐year‐old‐male who had undergone endoscopic ultrasound‐guided hepaticogastrostomy (EUS‐HGS) using an 8 × 100‐mm partially covered metal stent (MS) (Modified Giobor stent; Taewoong Medical, Seoul) for obstructive jaundice 1–4 due to unresectable gallbladder cancer after failed endoscopic retrograde cholangiopancreatography (ERCP) owing to duodenal invasion was admitted because of the second recurrent biliary obstruction (RBO). The first RBO developed due to hyperplasia at an uncovered portion and was treated with adding an uncovered MS 3 months prior.…”
Section: Figurementioning
confidence: 99%
“…A 66‐year‐old‐male who had undergone endoscopic ultrasound‐guided hepaticogastrostomy (EUS‐HGS) using an 8 × 100‐mm partially covered metal stent (MS) (Modified Giobor stent; Taewoong Medical, Seoul) for obstructive jaundice 1–4 due to unresectable gallbladder cancer after failed endoscopic retrograde cholangiopancreatography (ERCP) owing to duodenal invasion was admitted because of the second recurrent biliary obstruction (RBO). The first RBO developed due to hyperplasia at an uncovered portion and was treated with adding an uncovered MS 3 months prior.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, Iwashita et al . reported that EUS‐BD was comparable to PTBD in terms of efficacy and safety for distal biliary obstruction due to a malignant tumor 14 . Considering these facts, we prefer the EUS‐BD approach to the PTBD approach, after ERCP‐BD failure.…”
Section: Introductionmentioning
confidence: 97%
“…EUS-guided hepaticogastrostomy (EUS-HGS) is one of the EUS-BD techniques in which trans-gastrointestinal drainage is performed on the dilated intrahepatic bile duct due to MBO ( Figure 1 a). Additionally, the usefulness of EUS-guided antegrade stenting (EUS-AS) combined with EUS-HGS (EUS-HGAS) has also been reported ( Figure 1 b) [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%